STUDIES ON THE APPLICATION OF HOLLOW FIBER MEMBRANES IN THE FIELD OF ULTRAFILTRATION - LAURENȚIU TATARU; VALENTIN NEDEFF; NARCIS BARSAN; MIRELA PANAINTE-LEHADUS; EMILIAN MOSNEGUTU; DANA-ALEXANDRA CHITIMUS (Journal of Engineering Studies and Research)
This study is a review of knowledge and understanding of organic fiber membrane behavior in wastewater ultrafiltration processes. Current research is increasingly focusing on the use of state-of-the-art technologies for the elimination of pollutants in water and the use of membranes. This study focuses on testing hollow fiber organic membranes for the ultrafiltration process as a precursor to osmosis processes. The major advantages of ultrafiltration are the elimination of many small organic and inorganic compounds from the water, which cannot be eliminated in microfiltration processes, offering superior quality water. This review highlights the effectiveness of organic membranes from hollow fibers in relation to the dependence between filtering parameters and those related to the membrane type structure, respectively the membrane structure of the polyacrylonitrile. The results of the study on the testing of such membranes have shown that filtration efficiency increases inversely with the degree of fouling on the surface of the membrane; the permeate quality being superior in the early stages of the membrane lifecycle, decreasing with increasing use time. In other words, the aging of the membrane decreases the volume of the permeate and at the same time changes the dependence of the parameters: pressure, temperature, flow if it is desired to obtain the same amount of permeate. Finding the best solutions for streamlining the membrane structure and running under the best conditions will be presented in the current paper.